2002
DOI: 10.1074/jbc.m207472200
|View full text |Cite
|
Sign up to set email alerts
|

The Antifungal Protein AFP of Aspergillus giganteusIs an Oligonucleotide/Oligosaccharide Binding (OB) Fold-containing Protein That Produces Condensation of DNA

Abstract: The antifungal protein AFP is a small polypeptide of 51 amino acid residues secreted by Aspergillus giganteus. Its potent activity against phytopathogenic fungi converts AFP in a promising tool in plant protection. However, no data have been reported regarding the mode of action of AFP. The three-dimensional structure of this protein, a small and compact ␤ barrel composed of five highly twisted antiparallel ␤ strands, displays the characteristic features of the oligonucleotide/oligosaccharide binding (OB fold)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“…It comprises a chitin-binding domain and inhibits chitin synthesis in sensitive filamentous fungi (13). In collapsed and dead cells, AFP can also be found intracellularly (14,15), where it might bind via its oligonucleotide/oligosaccharide-binding fold to anionic molecules, such as nucleic acids (16). A shorter version of AFP exhibiting the chitin-binding domain but lacking the hydrophobic domain (sAFP) does not disturb the cell wall/ cell membrane integrity of AFP-sensitive filamentous fungi, although it is able to bind to chitin and nucleic acids under in vitro conditions (13).…”
mentioning
confidence: 99%
“…It comprises a chitin-binding domain and inhibits chitin synthesis in sensitive filamentous fungi (13). In collapsed and dead cells, AFP can also be found intracellularly (14,15), where it might bind via its oligonucleotide/oligosaccharide-binding fold to anionic molecules, such as nucleic acids (16). A shorter version of AFP exhibiting the chitin-binding domain but lacking the hydrophobic domain (sAFP) does not disturb the cell wall/ cell membrane integrity of AFP-sensitive filamentous fungi, although it is able to bind to chitin and nucleic acids under in vitro conditions (13).…”
mentioning
confidence: 99%
“…By comparison of the intron/exon structures of various alcohol dehydrogenase genes and related enzyme genes, Duester et al (1986) showed that the evolution of the oligonucleotide-binding domain was intron-dependent. A recent study indicated that AFP has the characteristic features of an oligonucleotide-binding domain (Martinez Del Pozo et al, 2002). In view of our current study and the evidence summarized above, it is tempting to speculate that the evolution of the AFP gene might be intron-dependent.…”
Section: Discussionmentioning
confidence: 58%
“…Mean residue weight ellipticities were expressed in units of degree x cm 2 x dmol -1 . All these determinations were performed under conditions described elsewhere [11,20,27].…”
Section: Characterization Of the Purified Proteinsmentioning
confidence: 99%
“…It displays the characteristic features of an oligonucleotide/oligosaccharide binding (OB-fold) structural motif [20] being a small and compact β-barrel composed of five highly twisted antiparallel β-strands. It should be also mentioned that cysteine pairing isomerism exists within its four disulfide bridges [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation